Concepts and terminology in organic stereochemistry - Kaloustian, Moses, 1944- (Elsevier, 2004)
In the last quarter century there have been only two seminal contributions in the field of organic stereochemistry - both by Kurt Mislow and his coworkers - ones that have clarified the basic concepts of stereotopicity and chirotopicity. Not withstanding a few other sporadic contributions by others, to date there have been no systematic attempts to unify and develop the conceptual framework and terminology of organic stereochemistry. Existing terms are frequently misused or abused, needed terms - redundant, confusing or controversial - are invented randomly, and yet other needed terms have not seen the light of day. This three-part work presents the elements of a simple, uniform and comprehensive language of the stereochemical underpinnings of organic chemistry. It is essential reading for industrial chemists, graduate students, university professors and industrial researchers in the field of Organic Stereochemistry. * Presents the elements of a simple, uniform and comprehensive language of organic stereochemistry. * Unifies and develops a comprehensive language of organic stereochemistry * Presents concepts and classifications which are universal.